Legal Anthropology and the Carok Tradition in Madura: A Study of Local Wisdom in Conflict Resolution - Moh. Rafi Maulana; Evi Dwi Hastri; Muhammad Khalid Ali (Res Judicata Law Review, 2024)
The carok tradition is still a debate among Madura scientists and culturers. The Carok tradition in Madura is a complex social phenomenon and is full of cultural values and local wisdom in conflict resolution. This article is not intended to discuss or assess carok from a moral point of view. On the contrary, this article only analyzes in the study of Legal Anthropology the phenomenon of carok from the perspective of the authorities in resolving an internal conflict and legal norms in society that are viewed as a form of violence and contrary to other general norms in society. The type of research used is sociolegal legal research. The approach used is an interdisciplinary approach, which combines methodologies and perspectives from social sciences, namely legal anthropology with legal analysis, such as the Madura carok tradition. The results of the study show that Carok is not only an act of violence, but also a symbol of honor and a recognized mechanism for the enforcement of customary law in the Madura community. The conflicts that lead to Carok are often triggered by violations of the norms of honor and self-respect, which are then resolved through physical duels as a form of social compensation. Although Carok is contrary to Indonesia's positive law that prohibits violence, the people of Madurese still view it as a legitimate and respectable way to resolve disputes. Thus, the legal anthropology approach is present as part of the interdisciplinary law to mediate the local wisdom owned by the Madurese people by understanding the social and cultural context behind the Carok practice, a more inclusive and sensitive policy can be developed.